PENERAPAN STRATEGI PEMASARAN BAGI PERUSAHAAN WARALABA UNTUK MENINGKATKAN VOLUME PENJUALAN di MASA PANDEMI COVID-19: (Studi Kasus Kopi Janji Jiwa di Bayeman Magelang) - Fitri Nurmalasari; Andhatu Achsa (Transpublika Publisher, 2023)
Sales are important for the sustainability of a business or business, when there is an increase in sales, profits can increase. A transaction or sale occurs when there is an interaction between a seller and a buyer. Conditions within the scope of the business or business competition market are getting tougher, this incident can be seen through several events every day. The purpose of this research is to help the position of Janji Jiwa in Magelang at this time and to know what strategy should be done in the future. The method used in this study is qualitative with SWOT analysis obtained from information sources in the field and from the distribution of questionnaires. In taking the sample using the Lemeshow formula because the population is unknown and infinite, so that in this sampling 100 respondents are needed. The results obtained from the assessment of internal and external factors are used for reference regarding current conditions and positions. From the internal factors obtained the results of 3.744, while the external factors obtained the results of 3.70. The position of Promise Soul is in quadrant 1 (progressive) which means that it has a strong strategy. So that the company has the strength and opportunity to develop the right strategy.